The Role and Mechanism of Deubiquitinase USP7 in Tumor-Associated Inflammation - Luhong Wang; Yong Zhang; Tao Yu; Huijian Wu (Biomedicines)
Deubiquitinating enzymes are a class of proteases that remove ubiquitin tags from proteins, thereby controlling protein stability and function. Tumor inflammation arises from interactions between tumor cells and their microenvironment, which trigger an inflammatory response. The deubiquitinating enzyme USP7 plays a central role in this process. Research suggests that USP7 may modulate various signaling pathways related to inflammatory responses through its deubiquitinating activity, thereby influencing tumor development and progression, including regulating T cell immune activity, improving macrophage anti-tumor activity, and regulating NF-κB signal pathways. Overall, describing the role and mechanism of USP7 in the tumor inflammatory response is of great importance for elucidating the regulatory mechanism of tumor inflammation and developing new therapeutic strategies. This article mainly reviews the structure, function, role, and mechanism of USP7 in the tumor inflammation response.